Quantitative Determination of Fluconazole by Ultra-Performance Liquid Chromatography Tandem Mass Spectrometry (UPLC-MS/MS) in Human Plasma and its Application to a Pharmacokinetic Study - Song, J.-j.; Li, W.; Wang, Z.; Tian, D.-d.; Yin, W.-y. (Drug Research, 2015)
In this study, a simple, rapid and sensitive ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method is described for determination of fluconazole (FLA) in human plasma samples using phenacetin as the internal standard (IS). Sample preparation was accomplished through one-step protein precipitation by methanol, and chromatographic separation was performed on an Acquity BEH C18 column (2.1 mm×50 mm, 1.7 μm) with mobile phase consisted of acetonitrile and water containing 0.1% formic acid (40:60, v/v) at a flow of 0.45 mL/min. Mass spectrometric analysis was performed using a QTrap 5500 mass spectrometer coupled with an electro-spray ionization (ESI) source in the positive ion mode. The MRM transition of m/z 307.2→238.2 was used to quantify for FLA. The linearity of this method was found to be within the concentration range of 10–6 000 ng/mL for FLA in human plasma. Only 1.0 min was needed for an analytical run. The method herein described was superior to previous methods and was successfully applied to the pharmacokinetic study of FLA in healthy Chinese volunteers after oral administration.
Keywords: fluconazole; UPLC-MS/MS; plasma; pharmacokinetic study